Comparison of load-carrying capacity, wear, and resource of metal-polymer corrected spur gears with a gear made of polyamides ??6 or PA6+30CF - Chernets, Myron (Strojniški vestnik, 2022)
Based on the developed calculation research method of metal-polymer gears the analysis of the influence of height and angular correction of engagement of spur gears on load-carrying capacity, linear teeth wear, and resources is carried out. Gears with a pinion made of carbon steel 0.45%C and a gear made of basic polyamide PA6 or carbon fibre composite PA6 + 30CF were investigated. Quantitative and qualitative patterns of influence of both types of correction, changes in the initial teeth profile due to wear, mating conditions on the load carrying capacity, teeth linear wear, and service life of investigated metal-polymer gears have been established. Profile correction causes a decrease in the contact pressure in the engagement by different amounts during the meshing cycle. They are most significantly reduced in the input area of two-pair engagement. It was found that when using PA6 + 30CF, the maximum contact pressures are about 1.29 times higher than with PA6 at all values of the shift coefficients, regardless of its type. The tooth linear wear has different values during the meshing cycle depending on the shift coefficients and parity of engagement. The resource first increases with increasing the shift coefficients, reaching their optimum, and then decreases again. Regularities of this influence for each type of correction of engagement are established. Metal-polymer gears with a gear made of PA6 + 30CF will have a significantly higher service life than with a gear made of PA6.
Keywords: height and angular correction of engagement; korektura ubirne višine in kota; kovinsko-polimerna čelna zobniška dvojica; linear teeth wear; linearna obraba zob; maksimalni kontaktni tlak; maximum contact pressures; metal-polymer spur gears; obstojnost zobnikov; poliamida PA6 in PA6 + 30CF; polyamides PA6 and PA6 30CF; resource